14. 13(y - 4) - 3(y - 9) = 5(y + 4)
Answers
Answer:
9
Step-By-Step Explanation:
L.H.S (Left Hand Side) = 13(y - 4) - 3(y - 9)
= [13y - (13x4)] - [3y - (9x3)]
= (13y - 52) - (3y - 27)
= 13y - 52 - 3y + 27 [Here, we multiply - into the bracket. So -(3y - 27) = -3y -(-27) = -3y + 27]
= (13y - 3y) - 52 + 27
= 10y - 25 ... Eq.1
R.H.S (Right Hand Side) = 5(y + 4)
= 5y + 20 ... Eq.2
Equating Eq.1 with Eq.2,
10y - 25 = 5y + 20
10y - 5y = 20 + 25
5y = 45
y = 45/5
y = 9
Please mark my answer as the brainliest...
Answer:
13y-52-3y+27= 5y +20
10y-27 =5y +20
10y -5y =20+27
5y =47
y =47/5
hope it helps you please mark me as brainliest